2011
DOI: 10.1203/pdr.0b013e31821ceb63
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Genetic Associations in the Inflammation, Complement, and Coagulation Pathways With Intraventricular Hemorrhage in LBW Preterm Neonates

Abstract: Intraventricular hemorrhage (IVH) is a significant morbidity seen in very low birth weight infants. Genes related to the inflammation, infection, complement or coagulation pathways have been implicated as risk factors for IVH. We examined ten candidate genes for associations with IVH in 271 preterm infants (64 with IVH grade I-IV and 207 without IVH) weighing less than 1,500 grams. The heterozygous genotype (odds ratio (OR)=8.1, confidence interval (CI)=2.5–26.0, p=4×10−4) and the A allele (OR=7.3, CI=2.4–22.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 40 publications
1
27
2
4
Order By: Relevance
“…It is noteworthy that many of these studies focused on genes related to coagulation and inflammation [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that many of these studies focused on genes related to coagulation and inflammation [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been previous studies about gene-environment interactions with relation to IVH [7, 25-28]. In twin studies, the difference in the incidence of IVH in monozygotic and dizygotic twins was not statistically significant [7].…”
Section: Discussionmentioning
confidence: 99%
“…In twin studies, the difference in the incidence of IVH in monozygotic and dizygotic twins was not statistically significant [7]. The study by Ryckman et al [28] suggested that the heterozygous Leiden mutation (RS6025) in coagulation factor V (F5) was associated with an increased risk of developing IVH grade I or II [28, 29]. A study performed in Germany demonstrated genetic predisposition in the protein C anticoagulant pathway in 66% of children with congenital porencephaly [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ryckman et al [24] included 271 very low birth weight infants born before 32 weeks of gestation. Ten genes potentially linked to increased IVH risk were isolated and examined, with specific single nucleotide polymorphisms selected for these candidate genes, based on previous research.…”
Section: Interleukin-1 (Il-1)mentioning
confidence: 99%